2009
DOI: 10.1212/wnl.0b013e3181b879be
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exchange for acute attacks of CNS demyelination

Abstract: Plasma exchange (PE) was associated with clinical improvement in 63% of patients at 6 months. Early initiation of PE and improvement at discharge were predictors of this response. Twelve patients (48%) who did not improve early did so during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
124
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(149 citation statements)
references
References 16 publications
18
124
2
3
Order By: Relevance
“…In three retrospective studies in a total of 87 patients with definitive diagnosis of MS and refractory relapses to high-dose steroids, it was reported that effective treatment was achieved with therapeutic plasma exchange in two-thirds of patients (79,80,81). The situation is different for acute isolated optic neuritis refractory to high-dose steroid and no benefit from therapeutic plasma exchange could be demonstrated.…”
Section: Plasmapheresismentioning
confidence: 99%
“…In three retrospective studies in a total of 87 patients with definitive diagnosis of MS and refractory relapses to high-dose steroids, it was reported that effective treatment was achieved with therapeutic plasma exchange in two-thirds of patients (79,80,81). The situation is different for acute isolated optic neuritis refractory to high-dose steroid and no benefit from therapeutic plasma exchange could be demonstrated.…”
Section: Plasmapheresismentioning
confidence: 99%
“…Неселективные методы экс-тракорпоральной гемокоррекции, как известно, на-шли широкое применение при рассеянном склерозе, а также других демиелинизирующих заболеваниях нервной системы. Эти методы достаточно давно при-меняются, обеспечивая более эффективное лечение [17,18], однако, в отличие от полуселективных ме-тодов, к которым относится каскадная плазмофиль-трация, имеют ряд недостатков. Так, плазмаферез за одну процедуру обеспечивает в среднем 20-30% замены объема циркулирующей плазмы, что тре-бует проведения не менее 3 процедур через 1-3 сут за 1 курс.…”
Section: российский вестник перинатологии и педиатрии 2 2016 Rossiyunclassified
“…Those patients who had not recovered early by PE (12 patients, 48%) did not get any better at follow-up. 74 A further retrospective review of 35 adult patients, concluded that 77% of steroid-resistant patients were improved after treatment with PE. 75 Successful use of PE was also described in some case reports including pediatric cases as well.…”
Section: Immunotherapeutic Approaches Of Chorea As Manifestation Of Omentioning
confidence: 99%